Isomerizing hydroformylation of cashew nut shell liquid - Pandey, Swechchha; Shinde, Dinesh R.; Chikkali, Samir H. (ChemCatChem, 2017)
A small library of bisphosphorus ligands was evaluated in the rhodium-catalyzed isomerizing hydroformylation (I-HF) of cashew nut shell liquid (CNSL). The rhodium complex of 1,2-bis((di-tert-butylphosphanyl)methyl)benzene (BDTBPMB; L4) outperformed the other bisphosphite and bisphosphine ligands and unveiled a moderate selectivity of 28% and 50% in the I-HF of CNSL monoene and methoxy-protected monoene, respectively. The resultant aldehyde 16-(3-methoxyphenyl)hexadecanal P1 was isolated and its identity was fully established. Application of bis-phosphine ligand L4 in the I-HF of highly challenging CNSL cardanol (S3) and methoxy-protected CNSL cardanol yielded a linear selectivity of 74%, although with reduced conversion. To demonstrate the synthetic utility of our strategy, the obtained aldehyde (derived from S3) was subjected to hydrogenation and the resultant 3-(16-hydroxyhexadecyl) phenol (P8) was isolated in 89% isolated yield. High-pressure NMR investigation revealed selective formation of a bis-equatorial BDTBPMB-rhodium complex, which might be responsible for the excellent linear selectivity.